A Comprehensive study of stress degradation pathways of Ascorbic acid to standardize Flavonoids-Related impurities derived from ascorbic acid (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Ascorbic acids are gaining popularity as functional food or health supplement owing to their antioxidant property. Ascorbic acid API or antioxidant ingredients was subjected to force degradation studies under various hydrolysis conditions as per the ICH guidelines i.e. acidic, alkaline, thermal, oxidative, and photolytic. The degraded samples were analyzed using a compatible self-developed HPLC method. The drug was found to be highly sensitive to alkaline environment and exhibited significant degradation. The drug has also shown degradation when exposed to oxidative stress. The drug was found to be quite stable in acidic, photolytic, and thermal conditions. The major degraded product obtained in alkaline condition was isolated, purified and characterized as (3S, 4R,5S)-3,4,5,6-tetrahydroxy-2-oxohexanoic acid with molecular mass of 194.14 g/mol and molecular formula of C6H10O7. This compound is a pharmacopeial impurity (EP impurity C) of the drug. This compound was then converted to its ester form to further ascertain its structural configuration. The ester was characterized as (3S, 4R, 5S)-methyl 3,4,5,6-tetrahydroxy-2-oxohexanoate (EP impurity D) with molecular mass of 208.17 g/mole and molecular formula of C7H12O7 The compounds were characterized with NMR, DMR, and mass spectroscopic technique. When ascorbic acid was subjected to oxidative stress, a water-soluble compound was obtained as the major degradant. Its isolation, identification and characterization are under study. A mechanism for the formation of (3S, 4R, 5S)-3,4,5,6-tetrahydroxy-2-oxohexanoic acid as the major degradant in alkaline stress was proposed.